Optical and visible and near-infrared fluorescence aspects of Er3+, Tm3+, and Nd3+-doped B2O3-rich glasses for fiber amplifiers and NIR lasers - G. Lakshminarayana; A.N. Meza-Rocha; O. Soriano-Romero; U. Caldiño; A. Lira; Dong-Eun Lee; Jonghun Yoon; Taejoon Park (Journal of Materials Research and Technology, 2022)
For synthesized each 1 mol% Er3+, Tm3+, and Nd3+-doped borate-rich glasses, optical and luminescence traits including fluorescence decay dynamics were explored. For Er3+: glass, at 1.4–1.65 μm range a wide NIR (near-infrared) luminescence band centered at 1.531 μm (4I13/2 → 4I15/2) and in Tm3+: glass, at 1.35–1.6 μm span a broad NIR fluorescence band centered at 1.458 μm (3H4→3F4) are obtained by 980 nm LD (laser diode) pumping (4I15/2 → 4I11/2) and 808 nm LD excitation (3H6→3H4) separately. Under 808 nm LD pumping (4I9/2 → 4F5/2+2H9/2), in Nd3+: glass, three emission bands peaked at 0.901 μm (4F3/2 → 4I9/2), 1.057 μm (4F3/2 → 4I11/2), and 1.329 μm (4F3/2 → 4I13/2) respectively are observed and in all such emissions, comparably the one obtained from transition 4F3/2 → 4I11/2 is highly intense. For acquired main visible and NIR emissions, Δλeff (effective bandwidth), by Füchtbauer–Ladenburg approach σemi (stimulated emission cross-section), gain bandwidth, and optical gain are evaluated. 75.73 nm, 113.67 nm, and 57.37 nm are the Δλeff values for Er3+: 4I13/2 → 4I15/2, Tm3+: 3H4→3F4, and Nd3+: 4F3/2 → 4I13/2 transitions accordingly. Using McCumber's theory, the calculated peak σemi for Er3+: 4I13/2 → 4I15/2 and Nd3+: 4F3/2 → 4I9/2 transitions are 1.495 × 10–20 cm2 and 0.5556 × 10–20 cm2, respectively. 4I13/2 → 4I15/2 transition gain cross-section spectra reveals C-band amplification at P (population inversion) = 50% in Er3+: glass, whereas at P = 30% for 4F3/2 → 4I9/2 transition gain cross-section is positive for lasing action at ∼0.9 μm in Nd3+: glass. All analyzed NIR luminescence outcomes reveal that studied glasses could be potential gain media for C-, S-, and O-bands fiber amplifiers and solid-state lasers.